ETR 300 : D’ Lima Cafe / Nor Aina Aisyah Mohd Arifuddin ... [et al.] - Mohd Arifuddin, Nor Aina Aisyah; Ahmad Khiri, Aina Naadhirah; Shafie, Muhamad Shakeer; Amrudin, Mohamad Aiman; Ghazali, Nur Adila (2014)
Our business type is based on foods, drinks and service. As name as D’Lima Café our mission and vision is to be the best hipster café in the town and deliver the best and luscious hipster dish for the customer with fresh and quality ingredients at an affordable price. D’Lima Café also is a business who thinks that customer satisfaction is our priority so that every customer we will give the best experience in our services. D’Lima Café is a partnership business which we have general manager, administration manager, marketing manager, production/operation manager and lastly financial manager. Their role in D’ Lima Café very important for example, general manager need to oversee daily business operations and hire worker then, administration manager responsibility to plan, coordinate and manage all procedures and system. The one who responsible for managing the company marketing initiatives is marketing manager while operation manager role is to managing activities that are part of goods and services. This business partner talented in their role so that the business can running smoothly and efficient in every time. Our business location address is at Jalan Taiping, 33000 Kuala Kangsar, Perak. There are many more idea to locate our business but this address is more suitable for D’Lima Café because it’s a strategic place which its location is the center of residency and easy to find and the location near to the main road so we make the decision to stand our café in this area because we can conclude that the ability to gain profit is high. In business the important things is gain profit and success in management so our café very emphasizing in handle every problem and issues faced by D’Lima Café. We use many strategy in order to attract the customer and some of the ideas are advertising, sales promotion and public relation and the idea was successfully raise profit day by day. We also care on our internal and external staff so they will work happy mood. It’s also one of our important priority in D’Lima Café. We in D’Lima Café hope that our business can make another branch in Malaysia so we can increase our profit and help unemployment people. We also want our café be the best cafe and successful business in Malaysia. We believe that our goals can be achieve based on our vision and mission in D’Lima Café.